The effect of different body mass index levels on static and dynamic postural balance performance in adults - TİMURTAŞ, EREN; SELÇUK, HALİT; DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN (My University, 2023)
Purpose: It was aimed to estimate the static and dynamic postural balance performance in adults with different Body Mass Index (BMI) levels. Material and Methods: The study was conducted in Üsküdar Diabetes and Obesity Treatment Center between September and October 2021. Participants were divided into 5 groups according to BMI scores: normal-weight, overweight, 1st degree obese, 2nd degree obese, and 3rd degree obese. In addition, participants' static and dynamic balance performance were assessed by the Limits of Stability (LOS) and modified Clinical Test of Sensory Integration of Balance (m-CTSIB) tests. Results: For LOS parameters, there was a significant difference between groups in reaction time scores only for the backward direction (p<0.05). The endpoint and maximum excursion measurements except for the backward and directional control measurements except for the back and right were significantly different between groups, with the worst scores for 3rd degree obese group (p<0.05). For the m-CTSIB test, there was a significant difference between groups in all parameters except the eyes open condition on foam surface (p<0.05). Conclusion: The 3rd degree obese individuals are the most affected subgroup in dynamic balance. We recommended that rehabilitation and fall prevention programs primarily focus on 3rd degree obese individuals. Keywords: Limits of stability test, modified clinical test of sensory integration of balance, postural balance, body mass index
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Health Sciences; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; Klinik Tıp; Klinik Tıp (MED); HEALTH CARE SCIENCES & SERVICES; CLINICAL MEDICINE; Clinical Medicine (MED); Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Gözden Geçirme ve Sınav Hazırlığı; Liderlik ve Yönetim; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Sağlık Politikaları; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); Review and Exam Preparation; Leadership and Management; Community and Home Care; Care Planning; Health Policy; Limits of stability test; modified clinical test of sensory integration of balance; postural balance; body mass index; OBESITY; IMPACT; STABILITY; WEIGHT; Limits of stability test; modified clinical test of sensory integration of balance; postural balance; body mass index